An in-silico investigation of Morita-Baylis-Hillman accessible heterocyclic analogues for applications as novel HIV-1 C protease inhibitors - Sigauke, Lester Takunda (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
Cheminformatic approaches have been employed to optimize the bis-coumarin scaffold identified by Onywera et al. (2012) as a potential hit against the protease HIV-1 protein. The Open Babel library of commands was used to access functions that were incorporated into a markov chain recursive program that generated 17750 analogues of the bis-coumarin scaffold. The Morita-Baylis-Hillman accessible heterocycles were used to introduce structural diversity within the virtual library. In silico high through-put virtual screening using AutoDock Vina was used to rapidly screen the virtual library ligand set against 61 protease models built by Onywera et al. (2012). CheS-Mapper computed a principle component analysis of the compounds based on 13 selected chemical descriptors. The compounds were plotted against the principle component analysis within a 3 dimensional chemical space in order to inspect the diversity of the virtual library. The physicochemical properties and binding affinities were used to identify the top 3 performing ligands. ACPYPE was used to inspect the constitutional properties and eliminated virtual compounds that possessed open valences. Chromene based ligand 805 and ligand 6610 were selected as the lead candidates from the high-throughput virtual screening procedure we employed. Molecular dynamic simulations of the lead candidates performed for 5 ns allowed the stability of the ligand protein complexes with protease model 305152. The free energy of binding of the leads with protease model 305152 was computed over the first 50 ps of simulation using the molecular mechanics Poisson-Boltzmann method. Analysis structural features and energy profiles from molecular dynamic simulations of the protein"“ligand complexes indicated that although ligand 805 had a weaker binding affinity in terms of docking, it outperformed ligand 6610 in terms of complex stability and free energy of binding. Medicinal chemistry approaches will be used to optimize the lead candidates before their analogues will be synthesized and assayed for in vivo protease activity.
Keywords: Protease inhibitors; Heterocyclic compounds; HIV (Viruses); HIV infections; Drug resistance; Cheminformatics